Assessing E-Leadership in the Public Sector during the COVID-19 Pandemic in ASEAN - Rahmad Agus Dwianto (Magister Administrasi Publik, 2021)
The COVID-19 pandemic period is a challenge for leaders, which has spurred the implementation of e-leadership, especially in the public sector. This article discusses changes in public sector e- leadership practices in ASEAN countries. The research was based on a qualitative research design. Data analysis used NVivo application on secondary data from various recent scientific articles and World Bank data. The results show that the practice of e-leadership in the public sector has experienced a multiplicity of changes that have affected several aspects including organizational culture, time management, use of information technology in carrying out tasks, and meeting media. Digital literacy, transparency, and time hours indicators are important in assessing the condition of e-leadership before and during the Covid-19 pandemic. Multitasking remains a challenge during crises. Leadership ability and knowledge of leadership in digital technology is one of key factors that influence success